Histomorphological and Histochemical Studies on Harderian Gland of Kadaknath Fowl - Verma, Rakhi (Indian Journal of Veterinary Anatomy, 2019)
Histomorphological and histochemical studies were conducted on the Harderian gland of the Kadaknath fowl at different age groups from day old to more than 32 week of age. The black coloured Harderian gland was situated ventral and postero-medial aspect of the eyeball. The Harderian gland was covered by thin connective tissue capsule and divided into different lobules of variable sizes by connective tissue trabeculae made up of mainly reticular fibers. The epithelium of corpus glandulae and excretory duct was lined by simple columnar epithelium of varying height. The apical portion of the glandular part was darkly stain and serous in nature while the basal portion was light stain and mucous in nature. Much amount of plasma cells, different sizes of lymphocytes, mast cells, macrophages and melanin pigments were present in the interlobular tissue of the gland. The activity for PAS and AMPS reaction was more towards the apex of the glandular unit than the base.